Analisis Kepuasan Konsumen pada Perdagangan Sayur Mayur - Moh. Tamrin; Sinar Hubtriyan Ade; Tiara Yuni Binugraheni (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Consumer satisfaction is an important factor in trade, with the creation of consumer satisfaction it can be used as the basis and reason for consumers to make repeat order. This study aims to find the effect of service, packaging and price perceptions on consumer satisfaction in the vegetable trade. This study uses a quantitative method using a descriptive analysis approach using questionnaire data and sampling by purpossive sampling. The results of the statistical analysis of the service variable t test obtained t count 2,587 > t table = 2,00030. The packaging variable has t count 3,111 > t table = 2,00030, and the Price Perception variable has t count 3,177 > t table = 2,00030. From the results of data analysis, it was concluded that the three variables, service quality, packaging and price perceptions had a positive and significant effect on vegetable customer satisfaction in Kopeng, Salatiga, Central Java.